Social determinants of breast cancer in the Caribbean: a systematic review - Catherine R. Brown; Ian R. Hambleton; Shawn M. Hercules; Miriam Alvarado; Nigel Unwin; Madhuvanti M. Murphy; E. Nigel Harris; Rainford Wilks; Marlene MacLeish; Louis Sullivan; Natasha Sobers-Grannum; The U.S. Caribbean Alliance for Health Disparities Research Group (USCAHDR) (BMC, 2017)
Abstract Background Breast cancer is the leading cause of cancer deaths among women in the Caribbean and accounts for >1 million disability adjusted life years. Little is known about the social inequalities of this disease in the Caribbean. In support of the Rio Political Declaration on addressing health inequities, this article presents a systematic review of evidence on the distribution, by social determinants, of breast cancer risk factors, frequency, and adverse outcomes in Caribbean women. Methods MEDLINE, EMBASE, SciELO, CINAHL, CUMED, LILACS, and IBECS were searched for observational studies reporting associations between social determinants and breast cancer risk factors, frequency, or outcomes. Based on the PROGRESS-plus checklist, we considered 8 social determinant groups for 14 breast cancer endpoints, which totalled to 189 possible ways ('relationship groups') to explore the role of social determinants on breast cancer. Studies with >50 participants conducted in Caribbean territories between 2004 and 2014 were eligible for inclusion. The review was conducted according to STROBE and PRISMA guidelines and results were planned as a narrative synthesis, with meta-analysis if possible. Results Thirty-four articles were included from 5,190 screened citations. From these included studies, 75 inequality relationships were reported examining 30 distinct relationship groups, leaving 84% of relationship groups unexplored. Most inequality relationships were reported for risk factors, particularly alcohol and overweight/obesity which generally showed a positive relationship with indicators of lower socioeconomic position. Evidence for breast cancer frequency and outcomes was scarce. Unmarried women tended to have a higher likelihood of being diagnosed with breast cancer when compared to married women. While no association was observed between breast cancer frequency and ethnicity, mortality from breast cancer was shown to be slightly higher among Asian-Indian compared to African-descent populations in Trinidad (OR 1.2, 95% CI 1.1-1.4) and Guyana (OR 1.3, 95% CI 1.0-1.6). Conclusion Study quantity, quality, and variability in outcomes and reporting limited the synthesis of evidence on the role of social determinants on breast cancer in the Caribbean. This report represents important current evidence on the region, and can guide future research priorities for better describing and understanding of Caribbean breast cancer inequalities.